Capacity analysis for MISO-UWOC systems over GGD weak turbulence with zero boresight pointing error - Yueheng LI; Yining XU; Meiyan JU; Ping HUANG (Tongxin xuebao)
Generalized Gamma distribution (GGD) was chosen to describe the weak oceanic turbulence, and a new hybrid fading channel model that integrated the GGD weak turbulence, the zero boresight pointing error, and the implicit path loss plus multipath propagation characterized by the fading free impulse response (FFIR) was proposed.Subsequently, mathematical expressions for the ergodic capacity and outage capacity of the multiple-input single-output underwater wireless optical communication (MISO-UWOC) systems were derived through the Meijer-G function under a selective transmission (ST) diversity scheme especially while inter-symbol interference (ISI) effects were considered or not.Finally, the correctness of the theoretical formulas derived above was verified by some numerical results.The simulation results show that with the introduction of the ST diversity, the ergodic capacity of the MISO-UWOC systems, taking the transmission ports N=2 as an example, is at least 1.3 times better than that of the conventional point-to-point (P2P) transmission under the same channel condition and system parameters, while the maximum outage capacity decreases is also more than 60% compared with the conventional P2P one.However, the introduction of the ISI will severely reduce this performance improvement.